Assessment of Flap Viability and Complication in Free Flap Reconstruction of Lower Third Leg and Foot Defects - Chakma, Subal Jyoti; Hossain, Abu Zaker; Turja, Agnibha Chakma; Paul, Rajib; Talukder, Dipankar Nath; Rahman, Hasib (Journal of Rangpur Medical College, 2026)
Background: Composite defects of the lower third leg and foot present significant reconstructive challenges due to limited local tissue availability, poor vascularity, and the frequent presence of exposed bone, tendon, or implants. Free flap reconstruction has become the preferred method for achieving durable coverage in this region yet flap viability and complication patterns may vary depending on patient factors, defect characteristics, flap type, and recipient vessels. Evidence from Bangladesh is limited despite the increasing burden of lower limb trauma and oncologic resections requiring microsurgical reconstruction. Objective: This study evaluated flap viability and early postoperative complications following free flap reconstruction of distal lower limb defects in a tertiary hospital setting. Methods: This prospective observational study was conducted in the Departments of Orthopedics and Burn & Plastic Surgery at Sylhet M.A.G. Osmani Medical College Hospital, Bangladesh, from July 2015 to June 2017. Eleven patients with composite defects of the lower third leg or foot requiring free flap coverage were consecutively enrolled. Data on patient demographics, comorbidities, defect etiology and site, flap type, flap size, and recipient vessels were collected prospectively. All free flaps were performed using standard microsurgical techniques, with postoperative monitoring following institutional protocols. Flap outcomes were categorized according to the Srikant classification. Minor complications included wound infection and partial graft loss, while major complications required surgical intervention. Descriptive statistics were used for analysis. Results: All 11 free flaps demonstrated complete survival, resulting in a flap viability rate of 100%. According to the Srikant classification, 72.7% of flaps achieved Grade 1 outcomes, 18.2% achieved Grade 2 outcomes, and 9.1% were Grade 3, reflecting partial non-critical losses. No cases of Grade 4 or Grade 5 flap failure occurred. Minor complications were observed in 18.2% of cases, and one major complication (9.1%) required secondary surgical management. The anterolateral thigh (ALT) flap was most commonly used (72.7%), while the anterior tibial artery served as the primary recipient vessel (81.8%). Neither flap type nor vessel choice showed a clear association with flap loss due to the overall high survival rate. Conclusion: Free flap reconstruction demonstrated excellent viability and low complication rates in patients with composite defects of the lower third leg and foot. The consistent success across flap types and recipient vessels highlights the reliability of microsurgical reconstruction in this region. J Rang Med Col.2026 Mar;11(1): 166-171